Pengembangan dan Validasi Lembar Kerja Peserta Didik (LKPD) Tema Udara berbasis Model RADEC dan berorientasi Keterampilan 4C - Yusup Maulana; Wahyu Sopandi; Atep Sujana; Babang Robandi; Nurul Saadah Agustina; Ika Rosmiati; Tri Pebriati; Jajang Bayu Kelana; Ida Fiteriani; Anugrah Ramadhan Firdaus; Linda Hania Fasha (Postgraduate, University of Mataram, 2022)
4C skills have become part of the current elementary school curriculum, which is expected to improve the quality of education so that graduates are ready to compete in the global world. Student worksheet, based on the RADEC model, is needed as a learning tool that can help participants practice 4C skills. This study aims to develop and validate the Student Worksheet based on the RADEC model on the theme of aerial skills-oriented 21st century: critical thinking, collaboration, creativity, and communication (4C). This research and development (R&D) use the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). This research was carried out until the development stage or validation stage. The validity of the student worksheet is determined by an assessment of media, materials, and language on a scale of four, validated by twenty-five teachers who have attended the RADEC model workshop for three days. The data obtained were tabulated by calculating the validity of the quantitative and descriptive analysis. The development results show that the student worksheet based on the RADEC model to train 4C skills is declared valid with the calculation results Vh>Vt or Vh> 0.64 and is suitable for use in learning. This research can be used as information on the development and validation of teaching materials, especially student worksheet, based on the RADEC model to train 4C skills in science materials in elementary schools.